Pengaruh Struktur Modal, Likuiditas, Kebijakan Dividen dan Good Corporate Governance Terhadap Nilai Perusahaan - Ziha Zahara Zetira; Tri Rachmat Riski (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of capital structure, liquidity, dividend policy, and good corporate governance, proxied by independent commissioners and institutional ownership, on firm value in mining companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study employed a quantitative approach with secondary data obtained from financial statements and annual reports. The research sample was determined using a purposive sampling technique, resulting in 10 companies as samples. Data analysis was performed using panel data regression with the assistance of STATA software. The results showed that capital structure and liquidity had a negative but insignificant effect on firm value. Independent commissioners and institutional ownership also showed a positive but insignificant effect. Meanwhile, dividend policy had a negative but significant effect on firm value. These findings indicate that investors in the mining sector prioritize long-term growth prospects over dividend distributions and the company's short-term financial condition. This study implies that companies need to be more careful in determining dividend policies to maintain their value in the market.